Technical Report on the request for technical assistance in relation to the safety of hydroxyanthracene derivatives. Issue 10 (20th October 2022) - ,; Aquilina, Gabriele; Bignami, Margherita; Bolognesi, Claudia; Crebelli, Riccardo; Dusinska, Maria; Gürtler, Rainer; Marcon, Francesca; Nielsen, Elsa; Schlatter, Josef; Vleminckx, Christiane; Nathanail, Alexis V; et al.
Abstract: In accordance with Article 31 of Regulation (EC) No 178/2002, the European Commission asked EFSA to provide technical assistance in the context of its 'Opinion on the safety of hydroxyanthracene derivatives for use in food' (EFSA ANS Panel, 2018). In this regard, EFSA was asked to assess whether the data from two new scientific publications presented by the Italian Society of Toxicology were sufficient to revise the conclusions of EFSA on the safety of hydroxyanthracene derivatives for use in food. The scientific publications under assessment were two in vivo comet assays in mice conducted on Aloe‐emodin and dried whole Aloe ferox juice, respectively. The results of the study with aloe‐emodin were considered inconclusive for the induction of DNA strand breaks with the standard comet assay protocol. Results obtained with the modified comet assay protocol with a lesion‐specific enzyme (hOGG1) suggest that aloe‐emodin can induce oxidative DNA damage in colon cells in vivo . The lack of DNA damage observed in the study on Aloe ferox juice was considered of low relevance with respect to the genotoxicity of hydroxyanthracene derivatives, because of the low concentrations of hydroxyanthracene derivatives and the potential counteracting effect of other components present in the juice (e.g. antioxidants). Based on the available evidence, EFSA concluded that the new information presented does not justify a revision of the conclusions of the EFSA ANS Panel Opinion on hydroxyanthracene derivatives.